Fluid Accumulation Zone by Seismic Attributes and Amplitude Versus Offset Analysis at Solfatara Volcano, Campi Flegrei, Italy - Gammaldi, Sergio; Ismail, Amir; Zollo, Aldo (Frontiers in Earth Science, 2022)
The imaging of volcanic systems is a challenging topic that attracts the scientific community’s attention. The characterization of structures and rock properties by means of seismic active methods is becoming fundamental for providing ultra-high-resolution images of the structures of interest. The Solfatara Volcano is a quiescent volcano in the Campi Flegrei resurgent nested caldera that is continuously under investigation and monitoring for its shallow activity, such as fumaroles. The purpose of this work is to characterize the fluid accumulation zone in the first 150 m depth in the middle of the crater, using several post-stack seismic attributes and Amplitude Versus Offset (AVO) analysis to characterize the contact between the CO2 and condensed water in the shallower accumulation zone. The two 400 m-long profiles to which we refer in this work have been acquired during the active Repeated InduCed Earthquakes and Noise experiment. The profiles were deployed along with the NNE-SSW and WNW-ESE directions across the whole surface of the crater including the main surface anomalies of the fumaroles, in the eastern area, and the mud-pool of Fangaia, located in the western area. The seismic pre-processing, pre-stack processing, and post-stack analysis previously applied on the NNE-SSW profile are here performed for the first time on the WNW-ESE profile, while partial-stack AVO analysis is performed for both profiles. The post-stack attributes including time gain, envelope, energy, and root mean square have been computed and extracted for determining the maximum and minimum values of amplitude zones on the migrated post-stack seismic profiles. Such anomalies are provided by complex and geometrical attributes embedding information on faults and chaotic zones. The AVO technique has also been used as a direct gas indicator to enhance fluid discrimination and identification. Finally, the analysis of the profile, seismic attributes, and near-surface structural interpretation related to the Solfatara Volcano has been incorporated into the proposed analysis. The multi-2D image depicts fluids trapped in the Solfatara Volcano at depths ranging from 10 to 50 m below the crater’s surface, as well as their migration paths up to 150 m deep: this evidenced contact between the fluids has been probably due to the solfataric alteration of the minerals, caused by the arising plume and the abovecondensed water which decreases the permeability of the rocks and forms an argillic phase working as cap-rock and trapping the gases. The application of the AVO analysis, coupled with the seismic attribute’s investigation, provides a very detailed multi-2D image of the shallower Solfatara Volcano, which outperforms in terms of accuracy the ones obtained with different tools in previous works, and that evidences the presence and the position of the liquid and the gases in the north-east area of the Solfatara Volcano.